Risk factors of late-onset gestational diabetes diagnosed during 24–28 weeks of gestation after normal early screening: a case–control study - Boriboonhirunsarn D. (2023)
Objective: To determine the risk factors associated with late-onset GDM (diagnosed between 24 and 28 weeks of gestation) after normal early screening. Methods: A case–control study was conducted in 600 singleton pregnant women who started antenatal care before 20 weeks with normal early GDM screening. Repeat screening was performed at 24–28 weeks. Cases were 120 women with late-onset GDM and 480 controls were those without GDM. Risk factors for late-onset GDM were evaluated and pregnancy outcomes were compared. Results: Cases were significantly older, and more likely to be overweight or obese. 50-g GCT of ≥ 160 mg/dL and abnormal 1 value of 100-g OGTT significantly increased the risk of late-onset GDM (p = 0.004 and < 0.001 respectively). Independent risk factors were abnormal 1 value of 100-g OGTT from first screening (adjusted OR 5.49, 95% CI 2.70–11.17, p < 0.001), age ≥ 30 years (adjusted OR 2.71, 95% CI 1.66–4.43, p < 0.001), DM in family (adjusted OR 1.76, 95% CI 1.07–2.88, p = 0.025), and BMI ≥ 25 kg/m2 (adjusted OR 1.86, 95% CI 1.17–2.97, p = 0.009). Late-onset GDM significantly increased the risk of preeclampsia, cesarean delivery, LGA, and macrosomia. Conclusion: Independent factors associated with late-onset GDM included abnormal 1 value of 100-g OGTT from first screening, age ≥ 30 years, DM in family, and being overweight or obese.